Total synthesis of an anticancer norsesquiterpene alkaloid isolated from the fungus flammulina velutipes - Kashinath, K.; Jadhav, Prakash D.; Reddy, D. Srinivasa (Organic & Biomolecular Chemistry, 2014)
The first total synthesis of a norsesquiterpene alkaloid (R)-8-hydroxy-4,7,7-trimethyl-7,8-dihydrocyclo-penta[e]isoindole-1,3(2 H,6H)-dione, isolated from the mushroom-forming fungus Flammulina velutipes, in both racemic and enantiomeric pure forms, is reported. The (-)-enantiomer of the natural product has been synthesized from the D-(-)-pantolactone chiral pool. The synthesis features a one-pot, three-step reaction sequence comprising an enyne RCM/Diels-Alder/aromatization to construct the desired indane skeleton present in the natural product. Our synthesis further confirms the assigned structure and absolute configuration of the natural product.

Total syntheses and biological evaluation of (+/-)-botryosphaeridione, (+/-)-pleodendione, 4-epi-periconianone B, and analogues - Handore, Kishor L.; Jadhav, Prakash D.; Hazra, Bibhabasu; Basu, Anirban; Reddy, D. Srinivasa (ACS Medicinal Chemistry Letters, 2015)
The total syntheses of (+/-)-botryosphaeridione, (+/-)-pleodendione, (+/-)-hoaensieremodione, 4-epi-periconianone B, and their analogues have been accomplished for the first time. All the synthesized target compounds were screened in neural anti-inflammatory assays using LPS induced microglia cells (N9). Among them, compounds 1 and 21 were identified as potential lead compounds for further profiling.
Keywords: antineuroinflammatoty agents; bohyosphaeridione; Natural product; pleodendione; Total synthesis